Use of Mechanical Thrombectomy versus Tissue Plasminogen Activator in Low–Middle-Income Countries: A Meta-Epidemiological Analysis of Treatment Options and Social Determinants of Health - Lauinger, Alexa R.; Naik, Anant; Bah, Momodou; Eltinay, Minnatallah; Covell, Michael M.; Arnold, Paul M. (WFNS Journal, 2025)
Acute ischemic stroke (AIS) is the second leading cause of death worldwide, and the disease burden falls greatly on low- and middle-income countries (LMICs) with around 63% of the global incidence. Despite medical advancements in high-income countries, this disparity in outcomes persists in LMICs. The impact of socioeconomic factors has not been well explored on treatment accessibility for AIS.We completed a systematic review using PubMed, Scopus, and Web of Science with the search focused on outcomes of AIS in LMICs. A pooled meta-analysis was completed with these studies correlating variables to the use of tissue plasminogen activator (TPA) and mechanical thrombectomy (MT) treatment.About 46 studies were found for the use of TPA or MT for AIS in LMICs between 2007 and 2022. The percentage of the population living below 50% of the median income correlated with TPA use. MT use correlated with the median income, population density, average life expectancy, poverty–headcount ratio, and gross national income (GNI) per capita. Meanwhile, we found that both TPA and MT use insignificantly correlated with better in-hospital mortality and poor neurological outcome rates.This meta-regression analysis uniquely explores the relationship between socioeconomic parameters in LMICs and the use of specific AIS therapies. Country parameters related to wealth disparity and population density correlated with treatment use. Further research with data involving delay to treatment and the potential impact of dedicated stroke centers warranted investigating the role of treatment accessibility in improving AIS outcomes.
Keywords: acute ischemic stroke; low- and middle-income countries; social determinants of health; mechanical thrombectomy; tissue plasminogen activator